Respondent based fuzzy numbers in fuzzy decision making / Fairuz Shohaimay … [et al.] - Shohaimay, Fairuz; Ramli, Nazirah; Mohamed, Siti Rosiah; Mohd, Ainun Hafizah (2013)
There are many studies on fuzzy decision making that incorporated fixed fuzzy numbers from the literature. However, these fuzzy numbers do not explain the actual respondents' opinions which will affect the overall decision making results. Therefore. fuzzy numbers based on respondents should be developed beforehand to be integrated into the existing fuzzy decision making tool. This paper aims to develop triangular fuzzy numbers based on respondents' opinions. Then, these fuzzy numbers were adopted into fuzzy evaluation method used in a supplier selection problem. The ranking results were analysed using seven different sets of fuzzy numbers. It was found that there is a variation in the ranking result when using fuzzy numbers based on different group of respondents, particularly the ranking of supplier based on main criterion. Hence, future studies in fuzzy decision making should include fuzzy numbers built based on respondents as they provide more reliable outcomes.